Makanan Halal Pada Street Food: Halal Awareness, Halal Knowledge, Label Halal Terhadap Keputusan Pembelian (Studi Kasus Di Kota Malang) - R. Tanzil Fawaiq Sayyaf (Jurnal Ilmiah Ekonomi Islam, 2023)
Currently, the need for halal products has increased, from the fields of medicine, fashion, halal food, halal cosmetics, Islamic finance to Muslim-friendly tourism. Indonesia is ranked first in the world in consuming halal food in 2019. The high level of Muslim population triggers a high demand for halal food. As a Muslim, sometimes consuming food is not too thorough to see whether a product is halal for consumption or not. The purpose of this study was to determine the effect of halal awareness, halal knowledge, prices on purchasing decisions for halal food at street food. The sample used was 100 samples with the criteria of having bought food at street food. Why is research important, because with the emergence of the new halal label issued by BPJPH, the public will be even more selective in the process of choosing halal food, indeed a lot of research on halal has been carried out, but research focusing in the object under study is different. The research method used is quantitative with technical analysis of SEM-PLS data using SmartPLS software. The result showed that halal awareness (X1), halal knowledge (X2) and halal label (X3) had an influence on the purchasing decision (Y) of halal food on street food.